2016
DOI: 10.1159/000444788
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid TDP-43 in Frontotemporal Lobar Degeneration and Amyotrophic Lateral Sclerosis Patients with and without the C9ORF72 Hexanucleotide Expansion

Abstract: Background: TDP-43 is the main protein component of ubiquitinated inclusions in a subgroup of frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis (ALS) patients. The C9ORF72 hexanucleotide expansion is one of the main mutations associated with TDP-43 pathology in FTLD and ALS. Our aim was to analyze cerebrospinal fluid (CSF) TDP-43 levels and Alzheimer's disease biomarkers in FTLD and ALS patients and to test whether the C9ORF72 expansion carrier status affects these variables. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 24 publications
1
29
0
2
Order By: Relevance
“…No significant effect of age and disease severity on CSF TDP-43 levels were observed in any of the studied groups, with the exception of males tending to present with higher TDP-43 levels than females. A similar increase in CSF TDP-43 levels in males has been previously reported in a mixed group of ALS and FTD patients [20]. Of note, the present study is the first where a healthy control group was included, whereas in previous studies the control group comprised (either as a whole or in part) patients suffering from other neurological diseases [17,18,19].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…No significant effect of age and disease severity on CSF TDP-43 levels were observed in any of the studied groups, with the exception of males tending to present with higher TDP-43 levels than females. A similar increase in CSF TDP-43 levels in males has been previously reported in a mixed group of ALS and FTD patients [20]. Of note, the present study is the first where a healthy control group was included, whereas in previous studies the control group comprised (either as a whole or in part) patients suffering from other neurological diseases [17,18,19].…”
Section: Discussionsupporting
confidence: 81%
“…Two previous studies on CSF have also reported increased TDP-43 levels in ALS patients compared to neurological controls [18,19], while others found no difference using a different method (immunoblot) [17]. Junttila et al [20] also reported higher TDP-43 levels in ALS versus FTD in both sporadic and genetic (C9ORF72) cases.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In postmortem studies, TDP-43 inclusions are detected in approximately 97% of patients with ALS. Based on these findings, investigators have pursued TDP-43 as a biofluid biomarker for ALS [92][93][94][95]. If changes can be reliably detected in blood or CSF, TDP-43 could be a valuable biomarker for the majority of patients with ALS.…”
Section: Tar Dna-binding Protein Of 43 Kdamentioning
confidence: 99%
“…Recently, however, CSF TDP-43 (either alone or in combination with other markers such as tau) has emerged as a candidate biomarker of ALS and FTLD and its levels are increased in both conditions [11,12] . Extensive investigation in order to determine and optimize its diagnostic potential is currently under way.…”
mentioning
confidence: 99%